PENGARUH LABA AKUNTANSI DAN ARUS KAS TERHADAP RETURN SAHAM - Pupu Sopini (Universitas Batanghari Jambi, 2016)
The existence of information accounting profit and cash flow and its components became the main indicators noted investors who will infuse capital in shares. The existence of positive sentiment on investor will make stock prices go up, so it is believed to return shares surged anyway. The purpose of this research is to know the influence of the accounting profit and the total cash flow changes along with its components which include changes in operating cash flow, investment cash flow changes and changes in cash flow partially funding and simultaneous against return of shares.The type of research that is done is causal research, while the sample of this research are companies incorporated in stock LQ45 period 2005-2015. The data used are secondary data analysis using regression models and linear compounds. The results of this study indicate, changes accounting profit (∆ LAK) and changes in total cash flow (∆ TAK) simultaneously and does not give partial influence on stock return. This is because the model return gives only a weak explanation in testing the content of information of accounting data, in addition to basic accrual accounting profit on that doesn't have a better capability in estimating cash flows in the future.Keywords: accounting profit, cash flow, and total return stock.